Navigating the Virtual Classroom: The Mediating Role of Psychological Distress in the Association between Psychological Flexibility and Academic Burnout in Adolescent Students - Isanejad, Omid; Moradian, Salah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The challenges of the education period can put students under pressure and endanger their health, with academic burnout being one of the predictable outcomes. This research aims to investigate the relationship between psychological flexibility and academic burnout, considering the mediating role of psychological distress.Methods and Materials: The participants included 769 students (386 girls and 383 boys) who completed the Educational Burnout Questionnaire (MBI-SS), the Depression, Anxiety, and Stress Scale (DASS-21), and the Acceptance and Action Questionnaire 2nd Edition (AAQ-II).Findings: The structural model showed that psychological flexibility is negatively correlated with academic burnout, while psychological distress is positively correlated with academic burnout. Additionally, the results indicated that psychological distress mediates the relationship between psychological flexibility and academic burnout..Conclusion: Based on these findings, it is recommended that educational programs integrate psychological flexibility training into school curricula to help students manage stress and negative emotions related to their studies. Interventions targeting psychological distress as a key factor in academic burnout could also be beneficial.